Aging behaviour of encapsulated assemblies of epoxy resin under accelerated thermal cycling. Issue 3 (3rd April 2022) - Yan, Han; Wang, Pengli; Li, Ruiqi; Xu, Zhiwu
Abstract: Epoxy potting materials are inevitably exposed to cyclic temperature environments during use. Under temperature load, thermal stress concentration occurs inside the epoxy encapsulation layer and leads to interface debonding and resin cracking, which eventually leads to the failure of the encapsulated component. In view of this, the effects of thermal cycling on epoxy resin and its encapsulated assemblies were investigated in this work. The surface morphology was characterized by scanning electron microscope (SEM) and atomic force microscope (AFM), the mechanical properties were measured by the Shore hardness tester and universal electronic extensometer, and the differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were employed to explore the thermogravimetric and thermal stability of epoxy resin under thermal cycling. The electrical properties of encapsulated assemblies of epoxy resin were measured by broadband dielectric spectroscopy and breakdown voltage. Fourier-transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were used to characterize the changes of the epoxy molecular structure before and after thermal cycling. Based on the aforementioned results and analysis, an aging mechanism of epoxy resin under an alternating thermal cycle was proposed.